Intestinal goblet cell carcinoid presenting with recurrent sterile peritonitis in a patient on peritoneal dialysis: a case report. Issue 1 (December 2017) - Chen, Chih-Wei; Chu, Jan-Show; Hsieh, Li-Chun; Kao, Chih-Chin; Lin, Yen-Chung; Chen, Hsi-Hsien
Abstract Background Goblet cell carcinoid is a rare variant of appendiceal carcinoid with mixed endocrine and exocrine features. The most common symptom and signs are abdominal pain, acute appendicitis and palpable mass. Additionally, abdominal pain is common in patient on peritoneal dialysis, which may confound the diagnosis in such patient. Case presentation We report a 71- years- old woman on peritoneal dialysis that experienced several episodes of abdominal cramping pain and sterile peritonitis. She had one episode of severe pain and underwent an appendectomy for suspicion of appendicitis. Goblet cell carcinoid was diagnosed. She had no further abdominal pain after she received appendectomy. Conclusions Malignant dialysate was rarely reported in patient with peritoneal dialysis. However, goblet cell carcinoid can initially present with acute appendicitis, chronic intermittent abdominal pain and mimicking peritonitis. In systemically reviewing the literature, this is the first case report of sterile peritonitis with peritoneal dialysis caused by goblet cell carcinoid.